The Influence of the Economic Studentsâ Motivations and Language Learning Strategies towards Their English Achievement in STIE Muhammadiyah Palopo - Iksan, Muhammad; Dirham, Dirham (Universitas Cokroaminoto Palopo, 2018)
The aims of this research were: (1) to investigate the studentsâ motivations, (2) to investigate the language learning strategies (LLSs) that are used by the students, (3) to investigate the level of studentsâ LLSs usage, and (4) to investigate the influence of the studentsâ motivations and the level of studentsâ LLSs usage towards their English competence. This research gave descriptions about the studentsâ motivations, LLSs that are used by the students, and the level of studentsâ LLSs usage. The sample of this research was 111 students that were taken from three classes of the first year students from three study programs, i.e. Ilmu Ekonomi, Manajemen, and Akuntansi. This research revealed that the students were categorized into high motivated to learn English where 70 students (63%) had high motivation, 25 students (23%) had very high motivation, 13 students (12%) had medium motivation, and 3 students (3%) had low motivation. This research also found that the students were dominantly used metacognitive strategies (44%), followed by compensation strategies (18%), affective strategies (14%), social strategies (10%), cognitive strategies (8%), and the least used strategies were memory strategies (6%). For the level of the studentsâ language learning strategies usage, the researcher found that the students level were categorized into medium, where 78 students (70%) mediumly used the LLSs, 30 students (27%) highly used the LLSs, 2 students (2%) lowly used the LLSs, and 1 student (1%) very highly used the LLSs.